2011
DOI: 10.1088/1751-8113/44/15/152002
|View full text |Cite
|
Sign up to set email alerts
|

A complementary relation between classical bits and randomness in local part in the simulating singlet state

Abstract: Recently simulating the statistics of singlet state with non-quantum resources has generated much interest. Singlet state statistics can be simulated by 1 bit of classical communication without using any further nonlocal correlation. But, interestingly, singlet state statistics can also be simulated with no classical cost if a non-local box is used. In the first case, the output is completely biased whereas in second case outputs are completely random. We suggest a new (possibly) signaling correlation resource… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The complementarity between signaling and randomness in the context of nonlocality [60], based on techniques developed in [61], and first conjectured in [62,63], can be formulated analogously for contextuality, reported elsewhere. Similarly, one may consider the single-system analog of device-independent quantum cryptography [64][65][66][67], based on contextuality inequalities [68].…”
Section: Inputmentioning
confidence: 99%
“…The complementarity between signaling and randomness in the context of nonlocality [60], based on techniques developed in [61], and first conjectured in [62,63], can be formulated analogously for contextuality, reported elsewhere. Similarly, one may consider the single-system analog of device-independent quantum cryptography [64][65][66][67], based on contextuality inequalities [68].…”
Section: Inputmentioning
confidence: 99%
“…A dierent way for quantifying the random choice was provided by [92,93] (see also [94]). Reconsidering Eq.…”
Section: Random Choicementioning
confidence: 99%
“…Later in [3], it has been shown that Bell's locality condition can be thought of as a conjunction of two independent conditions namely outcome independence and parameter independence, popularly called no signaling, which restricts instantaneous communication between two spatially separated locations. In recent times, lots of interest have been found in simulating nonlocal correlations by violating these assumptions individually or collectively [4][5][6][7]; and in particular for singlet state correlation there exists several interesting simulation protocols [8][9][10][11][12][13]. Please note, in Bell scenario any nonlocal correlation can be simulated by violating only the no signaling assumption (i.e.…”
Section: Introductionmentioning
confidence: 99%